Managing Resources for Better Outcomes in a Special Autonomy Region : Aceh Public Expenditure Analysis Update 2008 - World Bank (World Bank, Washington, DC, 2012)
This public expenditure analysis for Aceh in 2008 states that the Government of Aceh has received a Special Autonomy Fund to give greater opportunities to build infrastructure and public services and promote economic development. Budget allocation for the provincial government and district went to the main sectors such as infrastructure, health and agriculture. Indicators of social output also show the improvement in the provision of public services. However, major challenges still remain. For one thing, progress in social outcomes in many cases was still below the national average. Furthermore, provincial governments and districts still can not confirm the budget in accordance with the schedule set by the regulations, or spend the budget fully in each budget year. In addition, several important issues related to the implementation of special autonomy funds are still to be defined clearly. In line with this, this report sets out the challenges and obstacles faced by the provincial government and districts in dealing with the allocation of the budget and financial management in Aceh. This report also provides recommendations to help resolve these challenges, by giving attention to special autonomy in the management of the Special Fund and the regional budget and validation process in Aceh.